Pengaruh Metode Pembelajaran Sosiodrama oleh Guru PAK terhadap Minat Belajar Pendidikan Agama Kristen dan Budi Pekerti Siswa Kelas V SD Negeri 2 Martoba Kecamatan Simanindo Kabupaten Samosir T.A 2024/2025 - Juni Romauli Sinaga; Nisma Simorangkir; Limmarten Simatupang; Boho Parulian Pardede; Raikhapoor Raikhapoor (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2024)
This study aims to determine the positive and significant influence between the Sociodrama Learning Method by PAK Teachers on the Interest in Learning Christian Religious Education and Character Education of Class V Students of SD Negeri 2 Martoba, Simanindo District, Samosir Regency. The research hypothesis is that there is a positive and significant influence of the sociodrama learning method on the interest in learning Christian religious education and character education of class V students of SD Negeri 2 Martoba, Simanindo District, Samosir Regency, Academic Year 2024/2025. The research method uses a quantitative descriptive inferential approach. The population of all students of Class V of SD Negeri 2 Martoba, Simanindo District who are Protestant Christians totaling 32 people as the research sample. The research instrument is a closed questionnaire. The questionnaire trial was conducted on 30 student respondents outside the research respondents, and its validity and reliability have been tested. The results of the data analysis show that there is a positive and significant influence between the Sociodrama Method on the Interest in Learning PAK and Character Education of Class V Students of SD Negeri 2 Martoba, Simanindo District, Samosir Regency, Academic Year 2024/2025: 1) Analysis requirements test: a) positive relationship test obtained rxy value = 0.862> rtable (α = 0.05, n = 32) 0.349, thus there is a positive relationship between variable X and variable Y. b) Significant relationship test obtained tcount value of 9.311> ttable (α = 0.05, dk = n-2 = 30) 2.04227 thus there is a significant relationship between variable x and variable y. 2) Influence test: a) Regression equation test, obtained regression equation Ŷ = 2.50 + 0.53X. b) Determination coefficient test (r2) = 74.3%. 3) Hypothesis testing using the F test obtained Fcount > Ftable (α = 0.05, dk numerator k = 2, dk denominator = n-2 = 32-2 = 30 ) namely 84.73 > 1.62, thus Ha is accepted and H0 is rejected.